1985
DOI: 10.1084/jem.162.3.902
|View full text |Cite
|
Sign up to set email alerts
|

A common major surface antigen on amastigotes and promastigotes of Leishmania species.

Abstract: Enzymatic surface iodination and biosynthetic labeling with [35S]methionine, combined with immunoprecipitation by sera from patients with different forms of Leishmaniasis revealed a 65,000 Mr glycoprotein as the immunodominant moiety in promastigotes and amastigotes of the nine Leishmania species and isolates examined. Sera from patients with one form of Leishmaniasis recognized this component strongly, not only in the homologous, but also in the heterologous species. In addition to the crossreactivity display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
5

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 39 publications
4
34
0
5
Order By: Relevance
“…Gp63 has been described to be important in cell-cell (host-parasite) interaction (30), cell infectivity (19,40), specific diagnosis (14), and immunoprotection (31,41). This molecule was also identified in the sera from patients with CL, mucocutaneous leishmaniasis, or VL (7,9,14,20,21,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gp63 has been described to be important in cell-cell (host-parasite) interaction (30), cell infectivity (19,40), specific diagnosis (14), and immunoprotection (31,41). This molecule was also identified in the sera from patients with CL, mucocutaneous leishmaniasis, or VL (7,9,14,20,21,26).…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluated the WB results for the presence of at least one of the diagnostic antigenic bands, the sensitivity was calculated to be 99.1%. The 63-kDa protein was identified as a glycoprotein by staining with periodic acid-Schiff, indicating that it could be the main promastigote surface molecule (molecular mass, 60 to 65 kDa) common to all Leishmania species (5,7,10,12,21). Gp63 has been described to be important in cell-cell (host-parasite) interaction (30), cell infectivity (19,40), specific diagnosis (14), and immunoprotection (31,41).…”
Section: Discussionmentioning
confidence: 99%
“…Little has been done thus far to characterize the molecules that the parasites in these groups may have in common. Of the several proteins and glycoproteins shared by the leishmania that cause human disease, a 63-65-kD surface antigen appears to be highly conserved among these species and subspecies as judged by serological cross-reactivity (7,14,15), and by DNA sequence analysis (our unpublished data). This antigen from L. chagasi appeared at 63-65 kD.…”
Section: Resultsmentioning
confidence: 99%
“…We chose a single Leishmania antigen, gp63, for these studies. gp63 is one of the most abundant molecules on the surface of the parasite (11,24). Previous studies by us and others have shown that this molecule can influence complement fixation and parasite adhesion to macrophages (6,10).…”
Section: Discussionmentioning
confidence: 99%